2020
DOI: 10.1371/journal.pone.0239385
|View full text |Cite
|
Sign up to set email alerts
|

Multiple drivers of the COVID-19 spread: The roles of climate, international mobility, and region-specific conditions

Abstract: Following its initial appearance in December 2019, coronavirus disease 2019 (COVID-19) quickly spread around the globe. Here, we evaluated the role of climate (temperature and precipitation), region-specific COVID-19 susceptibility (BCG vaccination factors, malaria incidence, and percentage of the population aged over 65 years), and human mobility (relative amounts of international visitors) in shaping the geographical patterns of COVID-19 case numbers across 1,020 countries/regions, and examined the sequentia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 21 publications
1
51
1
1
Order By: Relevance
“…Moreover, there has been substantial public support despite these strict public health and social measures [ 23 ]. Other potential reasons for the less severe COVID-19 surge in Africa are likely due to the generally younger age demographics in Africa [ 9 ], and the relatively warmer climate [ 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there has been substantial public support despite these strict public health and social measures [ 23 ]. Other potential reasons for the less severe COVID-19 surge in Africa are likely due to the generally younger age demographics in Africa [ 9 ], and the relatively warmer climate [ 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…COVID19 virus has the potential to harm us as we are constantly exposed to the virus while visiting public places like restaurants, retail stores, businesses, places of worship, public parks and gardens, and places of work. Exposure to the virus can trigger our immune system to react to the virus as it has high negative outcomes towards our body which has led to intense research and human clinical studies about effective COVID19 vaccination [41][42].…”
Section: Discussionmentioning
confidence: 99%
“…In the study, respondents were shown how previous participants have answered survey questions in their country regarding behavioral perception about COVID19 pandemic, vaccination drive, social distancing, preventive measures like wearing masks, hand washing, using sanitizers, etc [42]. The information to the respondents was provided in a randomized way during the survey which showed the descriptive norms of the respondents about acceptance of the vaccination.…”
Section: Figure 2: Country Wise Vaccination Acceptance Behavioral Patternmentioning
confidence: 99%
“…If more up to date age stratified IFR estimates become available, the analysis can be updated. The spread of disease through a population may also depend on international mobility, climate or regional susceptibility [25]. Finally, the association between the IFR clusters and the change in death rate trajectories between time points may be biased by socioeconomic factors or missing death rate trajectories in countries excluded due to low numbers of reported deaths.…”
Section: Discussionmentioning
confidence: 99%